The Bible and Cinema: Artistic-Literary Convergences - Brey, Petterson (Poligrafi, 2024)
From Northrop Frye's perspective, which views the Hebrew Bible as the foundational imagination behind the literary ideologies that shaped Western thought, this discussion aims to highlight some points of convergence between biblical literature and the narrative structure found in contemporary cinema, one of the most sophisticated storytelling mediums today. The theoretical framework for this exploration draws on the works of scholars such as (1) Robert Alter, (2) Daniel Marguerat and Yvan Bourquin, (3) Gary Yamasaki, and (4) David Bordwell, among others. As Adele Berlin points out, the narratives of the Hebrew Bible convey their message through both the form and content of the text. Building on this idea, the focus here is to demonstrate that beyond thematic parallels, the narrative structure of the Bible aligns methodologically with the storytelling techniques of modern cinema.